Trends in Ambulatory Physician Opioid Prescription in the United States, 1997‐2009. Issue 7 (9th January 2014) - Jeffrey Kao, Ming‐Chih; Minh, Lyly Cao; Huang, Grace Y.; Mitra, Raj; Smuck, Matthew
Abstract : Objective: To describe the changing practice pattern of opioid medication prescription by health care providers and its relationship to shifts in the incidence of back pain, demographics, and health care access. Design: Retrospective analysis of nationally representative databases. Setting: In silico. Participants: Patients who presented at a set of randomly selected health care facilities on the days of data collection. Methods: Nationally representative surveys from the Centers for Disease Control and Prevention (National Hospital and Ambulatory Medical Center Survey and National Ambulatory Medical Center Survey) were investigated for 3 ambulatory settings—emergency department (ED), primary care physician (PCP), and specialist physician offices—between the years 1997 and 2009. Diagnoses, prescription medications, insurance source, and demographics were determined. Weighted logistic regression modeling with the SAS program (SAS Institute, Cary, NC) was used to estimate 5‐year odds ratios (ORs) and covariate effects. Main Outcome Measurements: Diagnoses, prescription medications, insurance source, and demographics were measured. The relationships between opioid medication prescription and (1) the chief complaint and (2) back pain diagnoses were studied. Domain analysis was used to properly account for the stochasticity introduced by subset analyses. Results: From 1997 to 2009, increasing all‐diagnosis opioid prescription was accompanied by significant shifts in patient demographics and insurance access. For all‐diagnosis opioid prescription, after we adjusted for age, gender, race, and insurance source, the increase persisted at a 5‐year OR of 1.33, 1.29, and 1.53 for ED, PCP clinics, and specialist clinics (95% confidence interval 1.26‐1.41, 1.19‐1.40, and 1.37‐1.69), respectively. The increasing prevalence of back pain diagnosis was eclipsed by increasing opioid prescriptions, estimated at 5‐year ORs of 1.35, 1.38, and 1.75 for ED, PCP clinics, and specialist clinics (95% confidence interval 1.22‐1.48, 1.19‐1.61, 1.40‐2.19), respectively. Conclusions: In the United States, from 1997‐2009, (1) variable increases in opioid prescription across ambulatory care settings were not accounted for by changing demographics and health care access; (2) significant disparities existed in opioid prescription as a function of age, gender, race/ethnicity, and payer source; and (3) for back pain, increasing opioid prescription was not accounted for by changing incidence.